Nup62, associated with spindle microtubule rather than spindle matrix, is involved in chromosome alignment and spindle assembly during mitosis. (14th July 2016) - Wu, Zhige; Jin, Zhihua; Zhang, Xinhong; Shen, Na; Wang, Jinbo; Zhao, Yingxian; Mei, Lehe
Abstract: An increasing number of the active mitotic functions of nucleoporins in the distinct steps of mitosis have been assigned over the past few years. As one of FG‐repeats containing nucleoporins, Nup62 has been found to be involved in nuclear transport, cell migration, virus infection, and cell cycle regulation. However, the role and mechanism of Nup62 in mitotic regulation have not been fully revealed. In this paper, it was revealed that a fraction of Nup62 was associated with mitotic spindle microtubule instead of spindle matrix, and the localization of Nup62 in the mitotic spindle depended on its three coiled‐coil domains rather than Crm1, although Nup62 strongly interacted with Crm1 during mitosis. Moreover, depletion of Nup62 by small interference of RNA seriously induced the defects of chromosome alignment and spindle assembly although the bipolar spindle was observed in most of the Nup62 knock‐down cells. Notably, congression of polar chromosome defect was observed in more than 30% of Nup62 knock‐down cells. These findings revealed that Nup62 was a novel mitotic spindle associated nucleoporin and involved in chromosome alignment and spindle assembly.